THE GLUTATHIONE SYSTEM IS INVOLVED IN REGULATION OF TUMOR CELLS APOPTOSIS - N. V. Ryazantseva; O. L. Nosareva; Ye. A. Stepovaya; Ye. V. Zakirova; A. I. Naumova; O. N. Vesnina; Ye. V. Shakhristova; D. S. Orlov; V. D. Yakushina; V. V. Novitsky (Бюллетень сибирской медицины)
The research objective is to determine the role of the gluthatione system components in realization of the receptor pathway of Jukart tumor cell apoptosis.Apoptosis realization using FITC-labeled annexin V and propidium iodide as well as the amount of TNF R1- and Fas-presenting cells has been evaluated by flow cytofluorometry; activity caspase-3 registered a spektroflyuorimetrichesky method. The concentration of reduced and oxidated gluthatione has been determined by spectrophotometry.The material for the research was intact Jukart tumor cells and the ones incubated in the presence of a selective inhibitor of the key gluthatione synthesis enzyme – buthionine-sulfoximine.The research has shown that the gluthatione system plays an important regulatory role in activation of the receptor pathway of Jukart tumor cell apoptosis.The gluthatione system components are targets for activation of programmed cell death in tumor growth.